Richness of Termites and Ants in the State of Rio Grande do Sul, Southern Brazil - Elena Diehl (Universidade Estadual de Feira de Santana, 2014)
Previous studies on the effects of environmental factors, such as altitude, latitude, temperature, deforestation, forest fragmentation, fire, and flood on the community structure of termites and ants were conducted in various regions of Brazil; few of them were carried out in the southernmost Brazilian state of Rio Grande do Sul. Here we describe termites and ants diversity at different sites along the four geomorphologic units of this state. We recorded 16 taxa of termites, of which three are new state records, increasing to 19 the number of termite species known to occur in the state. Accordingly, we also found 73 species and 115 morphospecies of ants, of which only one was a new record, raising to 265 taxa the number of ant species known to occur in the state. As expected, we found a higher species richness of ants than termites. The low richness of both groups relative to other Brazilian regions could be a consequence of the subtropical to temperate climate in the state, since most portions of the state are below 30o latitude, the study areas be above 500 m altitude, and other environmental characteristics of each site. We suggest a positive relationship between species richness of termites and altitude, while ant richness indicated an inverse relationship. However, our data are not conclusive, due to the low number of replications in each altitude, particularly for termites. This study is unique in presenting an updated checklist of termites and ants in the state of Rio Grande do Sul.